Exploring Relationships Between Self-Efficacy and Self-Regulated Learning Strategies of English Language Learners in a College Setting - Lee, Daeyeoul; Allen, Matthew; Cheng, Lixia; Watson, Sunnie; Watson, William (Journal of International Students, 2020)
This study investigated the relationships between self-efficacy and self-regulated learning (SRL) strategies of English language learners (ELLs) in a college setting from a social cognitive perspective in order to understand how to better support international. Participants in this study were 117 ELL college students who enrolled in an English language course at a Midwestern university. The results of simple linear regression analysis showed that ELL college students’ self-efficacy significantly predicted their use of SRL strategies. In addition, the results of a one-way ANOVA indicated a statistically significant difference in the use of SRL strategies between ELL college students who had high self-efficacy and those who had low self-efficacy. Based on study results, implications and future research directions are discussed.